2008
DOI: 10.1111/j.1463-1318.2008.01511.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct photographic documentation of ileal mucosa in routine colonoscopy is not an independent valid or reliable proof of completion: quality assurance issues for the national colorectal cancer‐screening programme

Abstract: Currently, terminal ileal imaging is not a reliable mode of documenting complete colonoscopy. Using water insufflation or dye-spraying coupled with modifications in image acquisition technique may improve its reliability but these methods require further investigation before they can replace the use of caecal landmarks as completion parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Furthermore, if villi are not clearly illustrated after a single water flush, additional flushes should be performed until villi are adequately demonstrated. We believe that the failure to employ these techniques was the main reason for the unfavorable opinion of terminal ileum photodocumentation recently reported by Baraza et al [14]. However, it should also be noted that their study reported a retrospective analysis of only 49 colonoscopies, performed by a single endoscopist.…”
Section: Cecal Images Statistical Differencementioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, if villi are not clearly illustrated after a single water flush, additional flushes should be performed until villi are adequately demonstrated. We believe that the failure to employ these techniques was the main reason for the unfavorable opinion of terminal ileum photodocumentation recently reported by Baraza et al [14]. However, it should also be noted that their study reported a retrospective analysis of only 49 colonoscopies, performed by a single endoscopist.…”
Section: Cecal Images Statistical Differencementioning
confidence: 85%
“…Furthermore, it was not clear whether these photographs had been taken for the purpose of photodocumentation, and no standardized protocol for demonstrating villi was employed. However, in the few patients in whom water instillation was employed, increased accuracy of ileal identification was reported [14]. In summary, documentation of colonoscopy completion is an essential component of quality assurance in routine clinical practice.…”
Section: Cecal Images Statistical Differencementioning
confidence: 99%
“…Also, some may consider “seeing the cecum at a distance” as being equivalent to “having reached the cecum”. Many efforts have been made to provide objective confirmation of complete intubation 11 . So far, the use of supportive photo documentation prevails although a photo of the cecum at distance may be erroneously accepted as a proof of reaching the cecum.…”
Section: Discussionmentioning
confidence: 99%
“…Images of the ileocecal valve along with the triradiate fold and appendicular orifice provide convincing evidence of a completed colonoscopy. Terminal ileal images alone without cecal images may not be reliable evidence of the completion of colonoscopy 8 . Therefore, we chose cecal image documentation over terminal ileal image documentation as a marker of completion of the procedure.…”
Section: Discussionmentioning
confidence: 99%